Large-scale GWAS identifies multiple loci for hand grip strength providing biological insights into muscular fitness - Sara M. Willems (Nature Portfolio, 2017)
Hand grip strength as a proxy of muscular fitness is a clinical predictor of mortality and morbidity. In a large-scale GWA study, the authors find 16 robustly associated genetic loci that highlight roles in muscle fibre structure and function, neuronal maintenance and nervous system signal transduction.